Innovations in Impact Evaluation: What Have We Learned? Insights from the Gender-Sensitive Risks and Options Assessment for Decision Making (ROAD) to Support Work-in-Freedom Phase 2 - Ringler, Claudia; Ratna, Nazmun; Alvi, Muzna (Centre of Excellence for Development Impact and Learning, 2023)
Intervention and Evaluation • WiF-2 project: ILO reduces vulnerability to trafficking and forced labour of women and girls from South Asia across migration pathways leading to the care and garment sectors in Arab States • ROAD migration evaluation: How are female migrants’ options shaped by gender and what is the potential of empowerment intervention to reduce trafficking and forced labor? • Geographies: Countries of origin: Bangladesh & Nepal; Destination countries: Jordan & Lebanon